Targeting the JAK/STAT pathway in solid tumors - Qureshy, Zoya (J Cancer Metastasis Treat, 2020)
Aberrant activation of signal transducer and activator of transcription (STAT) proteins is associated with the development and progression of solid tumors. However, as transcription factors, these proteins are difficult to target directly. In this review, we summarize the role of targeting Janus kinases (JAKs), upstream activators of STATs, as a strategy for decreasing STAT activation in solid tumors. Preclinical studies in solid tumor cell line models show that JAK inhibitors decrease STAT activation, cell proliferation, and cell survival; in in vivo models, they also inhibit tumor growth. JAK inhibitors, particularly the JAK1/2 inhibitor ruxolitinib, sensitize cell lines and murine models to chemotherapy, immunotherapy, and oncolytic viral therapy. Ten JAK inhibitors have been or are actively being tested in clinical trials as monotherapy or in combination with other agents in patients with solid tumors; two of these inhibitors are already Food and Drug Administration (FDA) approved for the treatment of myeloproliferative disorders and rheumatoid arthritis, making them attractive agents for use in patients with solid tumors as they are known to be well-tolerated. Four JAK inhibitors (two of which are FDA approved for other indications) have exhibited promising anti-cancer effects in preclinical studies; however, clinical studies specifically assessing their activity against the JAK/STAT pathway in solid tumors have not yet been conducted. In summary, JAK inhibition is a viable option for targeting the JAK/STAT pathway in solid tumors and merits further testing in clinical trials.